Evangelism and the churches: nine essays - West, W. M. S. (Carey Kingsgate, 1958)
Evangelism in the early church / W.M.S. West -- The approach to the non-churchgoer / L.R. Misselbrook -- Preparation for evangelism / H. Mowvley -- Evangelism in a village / R.P. Taylor -- Evangelism in a new area / N.P. Wright -- Evangelism in a London suburb / H.S. Tymms -- Evangelism and the family / B. Green -- Evangelism among young people / E.T. Smalley -- Evangelism through Christian fellowship / G.C. Ottaway